Correlations between selected coordination motor abilities and technical skills of Greco-Roman wrestlers aged 14-15 - Gierczuk, D.; Sadowski, J. (Archives of Budo, 2009)
The aim of this study was to evaluate the correlations of selected indices of coordination motor abilities (CMA) and technical skills of Greco-Roman wrestlers. Material/methods: Twenty-one wrestlers of the Greco-Roman style representing the student sports club UKS "Dwójka" took part in the research. The age of the examined was 14-15, and their sports experience was between 2.5 and 4 years long. The correlations between 12 indices (describing 7 CMA) and 10 technical elements of wrestling used in a horizontal and vertical posture were analysed. Technical skills were evaluated by five highly qualified wrestling coaches. Results: It was confirmed that there occurred significant correlations between technical skills and most CMA examined in wrestlers. In 55.8% of the cases correlation coefficients of the examined relations were higher than 0.50, which indicates a strong connection. The strongest correlations were observed between elements of wrestling technique and kinesthetic differentiation, movement combining, motor adjustment, dynamic balance and partly time-space orientation. In turn, the largest amounts of significant correlations with CMA were noticed in the following technical elements: curve trunk grip throw with an arm, curve back trunk grip throw as well as arm grip back throw. Technical elements performed in a vertical posture revealed stronger correlations with CMA than those done in a horizontal posture. Conclusions: Strong correlations between technical skills and kinesthetic differentiation, movement combining, motor adjustment, dynamic balance and time-space orientation prove that these CMA are extremely important in a training process of beginning wrestlers. Therefore, we should pay attention to their development particularly at the earliest stages of training.